The Conditions of Democracy in Europe 1919-39
XV, 503 p.
Keywords: Why did democracy survive in some European countries between the wars while fascism or authoritarianism emerged elsewhere? This innovative study approaches this question through the comparative analysis of the inter-war experience of eighteen countries within a common comprehensive analytical framework. It combines (social and economic) structure- and (political) actor-related aspects to provide detailed historical accounts of each case which serve as background information for the systematic testing of major theories of fascism and democracy.